Comparison of Cognitive Function in Different Trimesters of Pregnancy - Robabeh Soleimani; Maryam Asgharnia; Mir Mohammad Jalali; Fatemeh Eslamdoust-Siahestalkhi; Seyyed Mousa Kafi Masule; Rahman Iranidoost-Haghighi; Maryam Kousha (Caspian Journal of Neurological Sciences, 2022)
Background: Although pregnancy is a normal function in women, it is considered as a stressful experience which is associated with many psychological and physical changes in pregnant women. Objectives: This study aims to investigate and compare cognitive function in different trimesters of pregnancy. Materials & Methods: This was a longitudinal cohort study. Participants were 76 pregnantwomen with a mean age of 30.09±6.23 years referred to Al-Zahra Hospital in Rasht, Iran during 2019-2020. Participants were assessed in three trimesters of pregnancy using the Wechsler Memory Scale (WMS) and Mini-Mental State Exam (MMSE). The multilevel mixed-effects linear regression and repeated measures ANOVA were used for data analysis. All analyses were done in SPSS software v. 19 and Stata v. 14. Results: The mean score of WMS was significantly lower in the third trimester (84.95±12.07) than in the first and second trimesters (89.34±13.13 and 88.72±13.24, respectively) (P=0.001). The results of linear regression analysis showed no significant difference in MMSE score between different trimesters of pregnancy (P>0.05), while the WMS score was significantly different between different pregnancy trimesters; the change in WMS score was statistically significant only in the third trimester (P= 0.04). Conclusion: No impairment in general cognitive function occur during pregnancy, but memory impairment may occur. In the third trimester, pregnant women have the poorest memory function.